Archeological and mtDNA evidence for Tropical Lowland migrations during the Late Archaic / Formative in northern Chile Evidencia arqueológica y de ADNmt para migraciones de Tierras Bajas Tropicales Durante el Arcaico Tardío/Formativo Temprano en el norte de Chile - FRANCISCO ROTHHAMMER; CALOGERO M SANTORO; ELIE POULIN; BERNARDO T ARRIAZA; MAURICIO MORAGA; VIVIEN J STANDEN (Revista Chilena de Historia Natural, 2009)
The influence of tropical lowland migrations on the emergence of cultural change in the Central Andes has been postulated in general terms since the beginning of last century (Tello 1929). Archeological and molecular genetic evidence, particularly agriculture of tropical cultigens and ancient mtDNA haplogroup typing in northern Chile, suggest a chronologically more precise relationship between both regions. We test in this article the hypothesis that the process of cultural transformation of prehistoric populations living on the coast and the desert valleys of northern Chile can be partially linked to gene flow from the eastern slopes of the Andes and/or from the tropical lowlands during the Late Archaic / Formative periods (ca. 3,500-2,000 B.P.). La influencia de migraciones desde las tierras bajas tropicales en la emergencia de cambios culturales en los Andes Centrales, ha sido propuesta en términos generales desde comienzos de la última década (Tello 1929). Evidencia arqueológica y genético molecular reciente, particularmente la agricultura de cultígenos tropicales y la haplotipificacion de ADNmt antiguo, obtenida en el norte de Chile, sugieren una relación cronológicamente más acotada entre ambas regiones. Contrastamos en este artículo la hipótesis que el proceso de transformación cultural de las poblaciones prehistóricas costeras y vallunas del norte de Chile podría explicarse parcialmente por flujos migracionales originados en la vertiente oriental de los Andes y/o en las tierras bajas tropicales durante el periodo Arcaico Tardío / Formativo Temprano (ca. 3,500-2,000 A.P.).